ANALISIS MOTIVASI DAN PERSEPSI GENERASI Z DALAM MEMILIH KARIR SEBAGAI ASN - Nur Kholifah; Andriyastuti Suratman (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to examine the motivation and perception of generation Z in choosing a career as a State Civil Apparatus (ASN), by highlighting the driving factors, obstacles, and image of ASN in the eyes of the younger generation. The method used is descriptive qualitative with a thematic analysis approach. Informants were selected through purposive sampling techniques as many as 15 people, consisting of final year students, fresh graduates, and young civil servants aged 20-26 years who showed interest in the ASN profession. The data collection technique was carried out through in-depth interviews. The results of the study show that the main motivation of Generation Z in choosing a career as an ASN is a guarantee of job security, social status, and long-term stability. However, some negative perceptions also emerge, such as a rigid bureaucracy, lack of challenges, and lower starting salaries compared to the private sector. However, the existence of digital transformation and bureaucratic modernization has begun to affect the views of some informants towards the ASN profession more positively. This research shows the need for a more adaptive ASN branding and recruitment strategy, relevant to the values and expectations of Generation Z. This research contributes to the development of public sector human resource management studies, especially related to the career preferences of the younger generation which are still understudied in the Indonesian context.